2008
DOI: 10.1053/j.gastro.2007.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Protection by Hypoxia-Inducible Factor Prolyl Hydroxylase Inhibition

Abstract: A number of recent studies have implicated tissue hypoxia in both acute and chronic inflammatory diseases, particularly as they relate to mucosal surfaces involving epithelial cells. In this context, a protective role for the transcriptional regulator hypoxia-inducible factor (HIF) was demonstrated through conditional deletion of epithelial HIF-1α in a murine model of colitis (J. Clin. Invest. 2004; 114:1098−1106. Here, we hypothesized that pharmacologic activation of HIF would similarly provide a protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
341
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 336 publications
(359 citation statements)
references
References 41 publications
15
341
2
1
Order By: Relevance
“…PHD3 mRNA is also expressed in many tissues but is most abundant in the heart and placenta [24,28]. In mouse intestinal mucosal tissue, we have found expression all three isoforms of PHDs with a distribution of PHD1< PHD2=PHD3 [22][23].…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 70%
See 3 more Smart Citations
“…PHD3 mRNA is also expressed in many tissues but is most abundant in the heart and placenta [24,28]. In mouse intestinal mucosal tissue, we have found expression all three isoforms of PHDs with a distribution of PHD1< PHD2=PHD3 [22][23].…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 70%
“…It is interesting to note that NF-κB activates transcriptional upregulation of HIF-1a mRNA indicating one level at which these two pathways interact to regulate hypoxia-dependent gene transcription Our results show that the PHD inhibition provides an overall beneficial influence on clinical symptoms (weight loss, colon length, tissue tumor necrosis factor-α/interferon-γ) in multiple murine models of colitis. These effects are most likely due to their barrier-protective function and enhancement of wound healing at the site of inflammation [22][23]. Taken together, these findings emphasize the role of epithelial HIF-1α during inflammatory diseases in the colon and may provide the basis for a therapeutic use of PHD inhibitors in inflammatory mucosal disease.…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 72%
See 2 more Smart Citations
“…While the underlying causes of IBD remain largely undefined, the fundamental defect involves a loss of intestinal epithelial barrier function. We and others have shown that pan-hydroxylase inhibitors such as dimethyl-oxalylglycine (DMOG) have a protective effect in murine models of colitis and thus represent a potential new therapeutic approach (13)(14). However, these studies did not identify which hydroxylase isoforms or effector pathways are involved.…”
Section: Introductionmentioning
confidence: 99%